Comparative analysis of operation time and intraoperative fluoroscopy time in intramedullary and extramedullary fixation of trochanteric fractures - Mitković Milan M.; Milenković Saša; Micić Ivan; Stojiljković Predrag; Kostić Igor; Mitković Milorad B. (Vojnosanitetski Pregled)
Background/Aim. Cephalomedullary and extramedullary methods are used for the internal fixation of trochanteric fractures. The usage of the third generation Gamma Nail (GN) is a gold standard in this kind of treatments. Self-dynamisable Internal Fixator (SIF) is an extramedullary implant for trochanteric fractures’ treatment. The aim of this study was to compare these two methods regarding operation time and intraoperative fluoroscopy time. Methods. A total of 89 patients with a surgical treatment of a trochanteric fracture were included in this study. There were two groups of patients – GN group (43 patients) and SIF group (46 patients). Results. Average operation times were 67.5 min (GN group) and 56.0 min (SIF group). Average intraoperative fluoroscopy times were 84.8 s (GN group) and 36.7 s (SIF group). The difference between the groups was statistically significant for both of the given parameters (p < 0.05). The correlation between operation time and intraoperative fluoroscopy time was confirmed in the SIF group (p < 0.05; r = 0.405), while it was not confirmed in the GN group (p > 0.05). There was a higher variability in the GN method than in the SIF method regarding the duration and type of repeated surgical maneuvers followed by X-ray checks. Conclusion. The number of planned surgical interventions per day could depend on the type of trochanteric fracture internal fixation (intramedullary or extramedullary). Certain additional analyses including radiation dose assessment are desirable to clarify if shorter intraoperative fluoroscopy time in the SIF method can have the influence regarding intraoperative X-ray protection clothing. If there is the need to activate dynamization in long femoral axis after initial static fixation in that axis, the SIF method provides its spontaneous activation several weeks after the surgery without the need neither for additional surgery nor for additional intraoperative fluoroscopy